Penerapan Permainan Puzzel Terhadap Kemampuan Mengenal Angka di TK Muslimat NU 42 Tarbiyatul Masyithoh - Sumiyati, Sumiyati; Risdianto Hermawan (Pimpinan Cabang Muhammadiyah Kramat Jati, 2024)
This study aims to determine the ability and level of effectiveness of children in recognizing numbers at TK Muslimat NU 42 Tarbiyatul Masyithoh which is still low. There are many ways that teachers can do to improve the effectiveness of children in recognizing numbers, one of which is by playing puzzles. According to Effiana Yuriastien S. Psi et al., puzzle games are games that can stimulate children's understanding of space, the ability to imagine something mentally, and the ability to solve problems. This type of research is qualitative descriptive research. The subjects of this study were students at TK MNU 42 Tarbiyatul Masyithoh and the object of the research was puzzle games. Data collection techniques were through observation, interviews, and documentation. Through the puzzle games played by students at TK MNU 42 Tarbiyatul Masyithoh, children played enthusiastically during learning activities. It was found that puzzle games at TK MNU 42 Tarbiyatul Masyithoh were able to improve children's cognitive abilities in solving problems and had an effect on the recognition of number symbols in children. In the research conducted, the puzzle game to recognize numbers is done by children sorting puzzle pieces and recognizing the colors on the puzzle pieces, from the series of processes, children are able to sort the puzzle pieces according to their respective shapes and sizes. In the puzzle game, children are trained to concentrate on sorting and pointing out the numbers on the puzzle, when playing children are able to work together with friends and children are able to share puzzle pieces with friends and patiently wait in line.